Effect of semaglutide on liver enzymes and markers of inflammation in subjects with type 2 diabetes and/or obesity. Issue 2 (10th June 2019) - Newsome, Philip; Francque, Sven; Harrison, Stephen; Ratziu, Vlad; Van Gaal, Luc; Calanna, Salvatore; Hansen, Morten; Linder, Martin; Sanyal, Arun
Summary: Background: Obesity and type 2 diabetes are drivers of non‐alcoholic fatty liver disease (NAFLD). Glucagon‐like peptide‐1 analogues effectively treat obesity and type 2 diabetes and may offer potential for NAFLD treatment. Aim: To evaluate the effect of the glucagon‐like peptide‐1 analogue, semaglutide, on alanine aminotransferase (ALT) and high‐sensitivity C‐reactive protein (hsCRP) in subjects at risk of NAFLD. Methods: Data from a 104‐week cardiovascular outcomes trial in type 2 diabetes (semaglutide 0.5 or 1.0 mg/week) and a 52‐week weight management trial (semaglutide 0.05‐0.4 mg/day) were analysed. Treatment ratios vs placebo were estimated for ALT (both trials) and hsCRP (weight management trial only) using a mixed model for repeated measurements, with or without adjustment for change in body weight. Results: Elevated baseline ALT (men >30 IU/L; women >19 IU/L) was present in 52% (499/957) of weight management trial subjects. In this group with elevated ALT, end‐of‐treatment ALT reductions were 6%‐21% ( P <0.05 for doses≥0.2 mg/day) and hsCRP reductions 25%‐43% vs placebo ( P < 0.05 for 0.2 and 0.4 mg/day). Normalisation of elevated baseline ALT occurred in 25%‐46% of weight management trial subjects, vs 18% on placebo. Elevated baseline ALT was present in 41% (1325/3268) of cardiovascular outcomes trial subjects. In this group with elevated ALT, no significant ALT reduction was noted at end‐of‐treatment for 0.5 mg/week, while a 9% reduction vs placebo was seen for 1.0 mg/week ( P = 0.0024). Treatment ratios for changes in ALT and hsCRP were not statistically significant after adjustment for weight change. Conclusions: Semaglutide significantly reduced ALT and hsCRP in clinical trials in subjects with obesity and/or type 2 diabetes.